Patty's Industrial Hygiene 2001
DOI: 10.1002/0471435139.hyg065
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality In Nonindustrial Occupational Environments

Abstract: Indoor air in occupied buildings is always more polluted from human‐sourced contaminants than the air outside the building. This is true for modern buildings constructed during the past decade as well as for primitive shelters erected centuries or millennia ago. It follows that a continuous source of outdoor air is required to prevent the degradation of indoor air from contaminants arising from people and their activities. This was realized historically by the inventors of roof vents for exhaust of fire smoke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…Indoor air quality (IAQ) has been designated as a significant health concern in both the USA and Europe (Morey et al 2001;Bernstein et al 2008a). Although not generally recognised, indoor air pollution is almost always higher than outdoors.…”
Section: Growing Concerns About Indoor Air Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indoor air quality (IAQ) has been designated as a significant health concern in both the USA and Europe (Morey et al 2001;Bernstein et al 2008a). Although not generally recognised, indoor air pollution is almost always higher than outdoors.…”
Section: Growing Concerns About Indoor Air Pollutionmentioning
confidence: 99%
“…Elmrini et al 2001;Vergara-Fernández et al 2007;De Visscher and Li 2008;Mudliar et al 2010;Lebrero et al 2012). Systems are now becoming highly developed (e.g.…”
Section: Phytoremediation and Horticultural Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 levels exceeding 1000 ppm above the ambient level (about 380 ppm) indicate low ventilation and/or crowding (ventilation rate <7 l/s/occupant) (Morey et al., 2011), which can increase concentrations from building emission sources and indicate excess humidity, a concern for biological contaminants. A total of 38 homes (30%) experienced at least 1 week during the study in which the median weekly CO 2 level exceeded 1380 ppm.…”
mentioning
confidence: 99%
“…Some studies [45][46][47] reported that the main factor in fungal growth is the moisture available in the substrate, which is measured as relative humidity on the surface where fungal growth occurs, usually expressed as water activity (a w ).…”
Section: Discussionmentioning
confidence: 99%